Victims, the Forgotten Party in the Criminal Justices System: The Perception and Experiences of Crime Victims in Kumasi Metropolis in Ghana - Ofori-Dua, Kwadwo; Onzaberigu, Nachinaab John; Nimako, Richard Kofi (Journal of victimology and victim justice (Print), 2019)
Crime victims are an integral part of the criminal justice system. There has been recurrent consensus of opinion that without crime victims there can be no effective prosecution. Nevertheless, most studies have been crime-offender-centred. This research explored the experiences of the crime victim in the criminal justice system. Methodologically, this study employed a qualitative technique, face-to-face interviews to collect data. Purposive, snowball, expert sampling techniques were used to select respondents. The study revealed that although most crime victims were satisfied at the reporting stage, they were dissatisfied getting to the end of the criminal justice system process. Victims of offences as robbery and defrauding wanted their monies back after the imprisonment of offender whilst victims of violent crimes like rape, assault and murder want compensation to foot medical bills and other losses they incurred. Victims generally perceive that prosecution and conviction given to perpetrators were not deterring enough. The findings showed that crime victims felt re-victimised by CJS officials; especially because they were not treated with human dignity and the victims had many interesting conceptions of ‘being treated with dignity’ and ‘not being treated with dignity. The study concluded that the CJS should administer justice expeditiously and should be more inclusive.